Current smoking predicts inadequate response to methotrexate monotherapy in rheumatoid arthritis patients naïve to DMARDs: Results from a retrospective cohort study - Floris, Alberto; Perra, Daniela; Cangemi, Ignazio; Congia, Mattia; Chessa, Elisabetta; Angioni, Maria Maddalena; Mangoni, Arduino Aleksander; Erre, Gian Luca; Mathieu, Alessandro; Piga, Matteo; Cauli, Alberto (Medicine (Baltimore), 2021)
Identifying predictors of inadequate response to methotrexate (MTX) in rheumatoid arthritis (RA) is key to move from a "trial and error" to a "personalized medicine" treatment approach where patients less likely to adequately respond to MTX monotherapy could start combination therapy at an earlier stage. This study aimed to identify potential predictors of inadequate response to MTX in RA patients naïve to disease modifying anti-rheumatic drugs.Data from a real-life cohort of newly diagnosed RA patients starting MTX (baseline, T0) as first-line therapy were analyzed. Outcomes, assessed after 6 months (T1), were defined as failure to achieve a disease activity score 28 (DAS28) low disease activity (LDA) or a good/moderate response to MTX, according to the European League Against Rheumatism (EULAR) response criteria. Logistic regression was used to assess the associations between baseline variables and the study outcomes.Overall, 294 patients (60.5% females, median age 54.5 years) with a median disease duration of 7.9 months were recruited. At T1, 47.3% of subjects failed to achieve LDA, and 29.3% did not have any EULAR-response. In multivariate analysis, significant associations were observed between no LDA and current smoking (adjusted odds ratio [adjOR] 1.79, P = .037), female gender (adjOR 1.68, P = .048), and higher DAS28 (adjOR 1.31, P = .013); and between no EULAR-response and current smoking (adjOR: 2.04, P = .019), age (adjOR: 0.72 per 10-years increases, P = .001), and higher erythrocyte sedimentation rate (adjOR: 0.49; P = .020). By contrast, there were no associations between past smoker status and study outcomes.In summary, in our real-life cohort of disease modifying anti-rheumatic drug naïve RA patients, current smoking habit independently predicts inadequate response to MTX. This, together with other independent predictors of response to treatment identified in our study, might assist with personalized monitoring in RA patients. Further studies are required to investigate whether smoking quitting strategies enhance the therapeutic response to MTX.